Development of a mobile radioxenon processing system for on-site inspections and the deployment in IFE14. (October 2016) - Zhou, Chongyang; Zhou, Guoqing; Feng, Shujuan; Huang, Dingwei; Zhao, Xinhua; Wieslander, J.S. Elisabeth; Khrustalev, Kirill; Yu, Xiaolong; Cheng, Ziwei; Wu, Rui; Zou, Ronghu
Abstract: A mobile radioxenon gas processing system (XESPM-III) was developed for on-site inspections—targeting deployment in the Integrated Field Exercise in Jordan 2014 (IFE14)—in order to monitor radioxenon isotopes ( 131m, 133, 133m, 135 Xe) from the subsoil and atmosphere. XESPM-III is composed of primarily three units, the sampling unit, the purification unit and finally the quantification unit. The function of the sampling unit is to pre-enrich xenon by removal of impurities in the gas sample, while the purification unit further purifies, separates impurities and prepares a small-volume sample with relatively high concentration of xenon gas—both stable and radioactive xenon (if present). The quantification unit quantifies the stable xenon which provides information of the gas recovery (yield) of the gas sampling and purification process. In one cycle (7.5 h) XESPM-III can process either two 4 m 3 volume samples or two pairs 2 m 3 samples each; 24 h maximum throughput is thus twelve 2 m 3 samples or six 4 m 3 samples; final purified gas sample volume is approx. 7 cm 3 (Xe + N2 used as carrier gas); gas recovery (yield) is >70%; radon removal coefficient is 10 −6 ; cross contamination between subsequent samples is <1%; Its flexible design, that does not include a spectrometry system, allows it to be used with various spectrometric systems (HPGe, beta-gamma coincidence) for the final measurement of the radioactive xenon concentrations in the sample. During the field deployment of the XESPM-III in IFE14 it was able to measure 133 Xe in the range of 0.18–0.54 Bq/m 3 in spiked subsoil gas. Highlights: A On-site inspection radioxenon processing system was developed. 2 × 2 m 3 samples can be combined into 1 × 4 m 3, and with a high daily throughput. XESPM-III processed spiked subsoil gas samples with the measurements of 133 Xe in the range of 0.18–0.54 Bq/m 3 . The system carrier gas is N2 (5.0).